2023
DOI: 10.1002/advs.202204866
|View full text |Cite
|
Sign up to set email alerts
|

Codelivery of BCL2 and MCL1 Inhibitors Enabled by Phenylboronic Acid‐Functionalized Polypeptide Nanovehicles for Synergetic and Potent Therapy of Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) is the most refractory hematologic malignancy characterized by acute onset, rapid progression, and high recurrence rate. Here, codelivery of BCL2 (ABT199) and MCL1 (TW37) inhibitors using phenylboronic acid-functionalized polypeptide nanovehicles to achieve synergetic and potent treatment of AML is adopted. Leveraging the dynamic boronic ester bonds, B-N coordination, and 𝝅-𝝅 stacking, the nanovehicles reveal remarkably efficient and robust drug coencapsulation. ABT199 can induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…46 TM-VS significantly reduced hemolysis to less than 5% at SOR concentrations ranging from 1 to 100 μg/mL, which was in sharp contrast to free VS (****p < 0.0001) bearing a rate up to 100% (Figure 4D). The encapsulation of inhibitors by TM significantly improved drug hemocompatibility, which is in line with the results of other studies, 43,47 and offers the potential for intravenous administration of ) into NSG mice, similar to our previous reports. 48 Ex vivo imaging revealed that TM-Cy5 efficiently accumulated in the hind/fore-limbs, liver, and spleen of mice where the leukemia cells highly enriched, at 8 h after i.v.…”
Section: 4supporting
confidence: 91%
“…46 TM-VS significantly reduced hemolysis to less than 5% at SOR concentrations ranging from 1 to 100 μg/mL, which was in sharp contrast to free VS (****p < 0.0001) bearing a rate up to 100% (Figure 4D). The encapsulation of inhibitors by TM significantly improved drug hemocompatibility, which is in line with the results of other studies, 43,47 and offers the potential for intravenous administration of ) into NSG mice, similar to our previous reports. 48 Ex vivo imaging revealed that TM-Cy5 efficiently accumulated in the hind/fore-limbs, liver, and spleen of mice where the leukemia cells highly enriched, at 8 h after i.v.…”
Section: 4supporting
confidence: 91%
“…N 3 -PEG-PAPA was obtained through the ring-opening polymerization of α-aminopalmitic acid N -carboxyanhydride (APA-NCA) using N 3 -PEG-NH 2 ( M n = 5.0 kg/mol) as an initiator (Scheme S1), similar to the synthesis of mPEG-polypeptide in previous reports. As shown in Figure A, distinct 1 H NMR signals attributed to PEG (δ 3.85, 3.61) and PAPA (δ 4.62, 1.76, 1.27, 0.88) verified the characteristic structure of N 3 -PEG-PAPA. The degree of polymerization of the PAPA block determined by comparing the integral area of signals at δ 3.85 (methylene of PEG) and δ 0.88 (methyl peak of APA) was 19.2.…”
Section: Results and Discussionmentioning
confidence: 71%
“…Multiple large doses of CDDP or repeated administration within a short period of time may cause irreversible renal dysfunction and, in severe cases, lead to renal tubular necrosis. , Hesperetin (Hes), a kind of edible dihydroflavonoid compound that widely exists in citrus fruits, is easily available but with low solubility and bioavailability. Hes has been shown to have anti-cancer activity in gastric cancer, malignant glioma, prostate cancer, lung cancer, and other tumors by inhibiting cell proliferation and promoting cell cycle arrest or apoptosis. To achieve synergistic and potent treatment, the ideas of the co-delivery system have been designed and acquired remarkable therapeutic outcomes. , It has been reported that the combination of flavonoid compounds like Hes with 5-fluorouracil, CDDP, and paclitaxel can effectively improve the cytotoxicity of anti-tumor drugs. , In parallel, Hes can inhibit the PI3K/Akt signaling pathway and reduce the expression of matrix metalloproteinases (MMPs), an important mesenchymal cell marker, implicating that the combined administration of Hes with CDDP may achieve better inhibitory effects on tumor growth and metastasis if these two drugs could be specifically co-delivered to the tumor site efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…20−23 To achieve synergistic and potent treatment, the ideas of the co-delivery system have been designed and acquired remarkable therapeutic outcomes. 24,25 It has been reported that the combination of flavonoid compounds like Hes with 5-fluorouracil, CDDP, and paclitaxel can effectively improve the cytotoxicity of anti-tumor drugs. 26,27 In parallel, Hes can inhibit the PI3K/Akt signaling pathway 28 and reduce the expression of matrix metalloproteinases (MMPs), 29 an important mesenchymal cell marker, implicating that the combined administration of Hes with CDDP may achieve better inhibitory effects on tumor growth and metastasis if these two drugs could be specifically co-delivered to the tumor site efficiently.…”
Section: ■ Introductionmentioning
confidence: 99%